Effect of peripheral arterial disease on the onset of lactate threshold during cardiopulmonary exercise test: study protocol. Issue 12 (19th December 2016) - Key, Angela; Ali, Tamara; Walker, Paul; Duffy, Nick; Barkat, Mo; Snellgrove, Jayne; Torella, Francesco
Abstract : Introduction: Cardiopulmonary exercise test (CPET) is widely used in preoperative assessment and cardiopulmonary rehabilitation. The effect of peripheral arterial disease (PAD) on oxygen delivery (VO2 ) measured by CPET is not known. The aim of this study was to investigate the effect of PAD on VO2 measurements during CPET. Methods and analysis: We designed a prospective cohort study, which will recruit 30 patients with PAD, who will undergo CPET before and after treatment of iliofemoral occlusive arterial disease. The main outcome measure is the difference in VO2 at the lactate threshold (LT) between the 2 CPETs. The secondary outcome measure is the relationship between change in VO2 at the LT and peak exercise pretreatment and post-treatment and haemodynamic measures of PAD improvement (ankle–brachial index differential). For VO2 changes, only simple paired bivariate comparisons, not multivariate analyses, are planned, due to the small sample size. The correlation between ABI and VO2 rise will be tested by linear regression. Ethics and dissemination: The study was approved by the North West-Lancaster Research and Ethics committee (reference 15/NW/0801). Results will be disseminated through scientific journal and scientific conference presentation. Completion of recruitment is expected by the end of 2016, and submission for publication by March 2017. Trial registration number: NCT02657278.